DINAMIKA PENGATURAN GANTI KERUGIAN PADA PENGADAAN TANAH UNTUK KEPENTINGAN UMUM DARI PERPRES KEPADA UNDANG - UNDANG - SANIAH . (LP2MTBM MAKARIOZ, 2021)
Compensation is the dominant factor in land acquisition. In the regulations before the promulgation of law No. 2 of 2012, theissue of compensation of compensation for non-physical properties was not regulated. However, after the promulgation oflaw No.2 of 2012, the compensation has been regulated. Only the things that are classified as non-physical losses arelimited.